2021
DOI: 10.1037/cou0000541
|View full text |Cite
|
Sign up to set email alerts
|

“What American dream is this?”: The effect of Trump’s presidency on immigrant Latinx transgender people.

Abstract: Little research has explored how transgender people are impacted by the behaviors, statements, and policies of the Trump administration. To date no scholarship has explored the experiences of immigrant Latinx transgender people during the current political climate. Using a critical intersectional qualitative framework, the present study aimed to investigate how immigrant Latinx transgender people are impacted by Trump's administration. A community sample of 15 immigrant Latinx transgender people from a large m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…The four qualitative articles provided examples and context for the range of depressive symptoms Latinx individuals experienced between 2017 and 2021. Depressive symptoms reported by transgender Latinx adults and Latinx college students on DACA included hopelessness, helplessness, suicidal ideation, and feelings of sadness (Abreu et al., 2021; Moreno et al., 2021). In the sample of students on DACA, whom were asked to think about the emotional impact of political debates during the Trump administration, 33% reported depressive symptoms (Moreno et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four qualitative articles provided examples and context for the range of depressive symptoms Latinx individuals experienced between 2017 and 2021. Depressive symptoms reported by transgender Latinx adults and Latinx college students on DACA included hopelessness, helplessness, suicidal ideation, and feelings of sadness (Abreu et al., 2021; Moreno et al., 2021). In the sample of students on DACA, whom were asked to think about the emotional impact of political debates during the Trump administration, 33% reported depressive symptoms (Moreno et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…These studies discussed how protesting, speaking to elected officials, signing petitions, sharing personal immigrant narratives, educating others to dispel commonly held stereotypes, and choosing future careers that defend Latinx rights helped Latinx children, students and family's effect sociopolitical change and gain a sense of hopefulness (Arce et al, 2020;Martinez et al, 2021;Walsdorf et al, 2022;Wray-Lake et al, 2018). Finally, 53.3% Latinx transgender adults and 100% of DACA students reported pride in their intersectional identities despite debates to the contrary (Abreu et al, 2021;Moreno et al, 2021;. For example, one DACA student described her family's pride in being undocumented and its contribution to her work ethic and desire for others not to feel sorry for her.…”
Section: Mental Health Outcomes For Latinx-resilience Factorsmentioning
confidence: 99%
“…The authors wrote two other manuscripts from this dataset. One manuscript focused on how the current sociopolitical context under Trump’s presidency has impacted immigrant Latinx transgender people (Abreu et al, in press), and the other manuscript focused on immigrant Latinx transgender peoples’ resource wants and needs (Gonzalez et al, in press). The conceptualization, interview questions, and data analysis for the previously submitted manuscripts using this dataset are distinct from this manuscript.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we used a critical reflexive approach to thematic analysis by reflecting on our own positionalities and how our identities informed our analysis (see Braun & Clarke, 2013). Because of the pervasive erasure of immigrant Latinx transgender peoples’ experiences (see Abreu et al, in press), the authors were interested in making meaning of the participants’ lived experiences using their own narratives (Braun & Clarke, 2006). Thematic analysis allowed the authors to center the experiences of the participants by analyzing patterns found in the data.…”
Section: Methodsmentioning
confidence: 99%
“…We propose that institutions of higher education must, regardless of the political climate at the time, unequivocally support the needs of LGBTQ+ students on campus. In fact, because of the negative effects that oppressive political climates have on the well-being of LGBTQ+ individuals (Abreu et al, 2021;Gonzalez et al, 2018Gonzalez et al, , 2022, we believe that institutions of higher education must invest in the well-being of LGBTQ+ students across campus. For example, now more than ever colleges and universities should require safe zone trainings for all faculty, staff, and students.…”
Section: Unapologetically Support and Expand Equity Diversity And Inc...mentioning
confidence: 99%